The effect of science centres on perceptions of secondary school students towards the nature of science - Efe, Hacer; Topsakal, Unsal Umdu (EDUCATION ASSOC SOUTH AFRICA, 2022)
In the study reported on here, the effects of science centres on the perceptions of secondary school students towards the nature of science were examined. The study group consisted of 16 students aged 13 and 14 of which 7 were female and 9 male. In this study, a total of 4 trips were arranged to the science centre twice a month for 2 months. Students attended different workshops, planetariums and exhibitions on each trip to the science centre they attended. The activities that students attended during these trips were independent of the school curriculum. The data were obtained in the spring of 2019. This study was experimental research. Mixed method was used as the research model and the concurrent triangulation pattern was used as the design. The Scientific Knowledge Scale, the Questionnaire for Scientific Knowledge and semi-structured interviews were used as data collection tools, which were administered to students before and after the activities. In data analysis, qualitative data were analysed using content analysis. Quantitative data were analysed using the SPSS program. As a result of the research, it was determined that science centres caused an increase in students' scores and levels of scientific knowledge and an improvement in their views on the nature of science.
Keywords: learning environments; nature of science; out-of-school learning; perception; science; science centres; secondary school; student; TEACHERS NATURE; TEACHING NATURE; EDUCATION; VIEWS; UNDERSTANDINGS; INSTRUCTION; CONCEPTIONS; TECHNOLOGY; KNOWLEDGE; LITERACY; Education & Educational Research